Thematic Analysis: Human Resource Management in Verses of The Qur'an - Sutrisno , Andri; Mudarris, Mudarris (LPPPM STAI Darul Hikmah Bangkalan, 2021)
Human resource management is a process of managing human resources or a potential within humans to realize desired goals in groups. In the Qur'an, it is explained that man is the creation of Allah Almighty. Who is perfect from other beings. Management science is part of the social film, so it is very closely related to human resources. The most influential actor in the management process is the man himself. So that human resource management becomes critical in success to achieve the goals aspired by each group. Islam is a religion that provides various solutions for human affairs, especially in the process of human resource management in its holy book, the Qur'an. Thus in this article, researchers use literature research that examines and analyzes books related to human resource management from the perspective of Quranic verses. So it can be concluded that in the management of human resources in the verses of the Qur'an, there are four processes, namely planning, selection and placement, development, and compensation.